Clinical supervision in nursing: effective pathway to quality - Cruz, Sandra (2011)
Effects of clinical supervision on the quality of care are a key aspect in the improvement of quality and they were defined as target area by the World Health Organization (Hyrkäs & Lethi, 2003). The aim of this exploratory, descriptive and longitudinal study was to develop a clinical supervision in nursing model that bestsupports the nurses’ professional practice. The research was done in several health institutions. With this article we pretend to publicize the results of the application of the Portuguese version of the Manchester Clinical Supervision Scale© after the implementation of our clinical supervision in nursing model.